Mountain civilizational nodes of Altai and the Caucasus in sociocultural dynamics and local dimensions - Ivanov, Andrey V.; Popkov, Yuri V. (The New Research of Tuva, 2026)
The article substantiates the idea of “mountain civilizational nodes” and their important, often ambiguous, role in the interaction and development of peoples and civilizations, the life of local communities. It presents the experience of using a comparative approach (in its general and panoramic dimension) in a comparative analysis of the mountain territories of Altai and the Caucasus. The emphasis is placed on comparing their geopolitical and ethnocultural potential. A preliminary characterization is given of the elements of similarity and of the specific features of the geological and biospheric resources of these regions. It is noted that in these parameters the Caucasus is more similar to the Himalayas than to Altai. The visibility of the parallels between Altai and the Caucasus in historical geopolitics is determined by their significant importance as mountainous border territories in the interaction of the megacivilization of the East, primarily represented by Turkey and China, and the megacivilization of Northern Eurasia represented by Russia. Whereas in Altai the civilizational and geopolitical influence of Russia on local peoples and communities was carried out mainly by non‑violent means, in the Caucasus this process unfolded in a more complex and dramatic way. However, in both directions Russia’s integration policy implied the preservation of the cultural and religious distinctiveness of local peoples. The effectiveness of the state’s literary and cinematographic policy in the Soviet period in strengthening intercultural dialogue among different peoples is emphasized. The current situation, from the standpoint of actual peacebuilding potential, is assessed as favorable in Altai and problematic in the Caucasus. The authors link the prospects for the development and interaction of people with the need to overcome the temptations of all forms of fundamentalism and nationalism. The idea of Eurasian brotherhood of peoples and the right of each of them to preserve its national culture and ethnocultural uniqueness should become fundamental. The article also touches upon issues related to existing environmental problems of Altai and the Caucasus and their sacral significance for the local population. It is concluded that, considering the significant role of mountain territories in the development and interaction of peoples and cultures, the development and implementation of a special state program for mountain regions is an urgent task.